TI_GERICHTE 11.2010.103 vom 4. Dezember 2012 , Infiltrazioni d'acqua da un fondo sovrastante: deflusso naturale delle acque - TI Tribunale d'appello (2012)
Infiltrazioni d'acqua da un fondo sovrastante: deflusso naturale delle acque